Pedestrian choice behavior analysis and simulation of ticket gate machine in rail transit station - Li, Yongxing (2021)
Considering pedestrian preferences for the minimum distance, the minimum number of queuing pedestrians and the shortest estimated time, three pedestrian choice strategies of ticket gate machine are proposed. Pedestrian choice strategies of ticket gate machine are added into pedestrian simulation model which is based on cellular automata, and pedestrian choice behavior simulation model of ticket gate machine is obtained. On the platform of MATLAB simulation software, pedestrian choice behavior is simulated. Simulation results indicate that choice strategies of ticket gate machine proposed in this paper describe pedestrian choice behavior well, and it needs to consider the ratio of bidirectional pedestrian generation rate in the process of setting ticket gate machines in the bidirectional passage.